2020
DOI: 10.3399/bjgpopen20x101009
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate medications in older patients based on Beers criteria: a cross-sectional study of a family medicine practice in Saudi Arabia

Abstract: BackgroundThe use of potentially inappropriate medications (PIMs) is an important issue in older patients who are at risk of adverse drug events.AimTo determine the prevalence of PIM use, according to Beers criteria, among an older population (aged ≥65 years) in a large family medicine setting, and to identify the associated risks.Design & settingA prospective cross-sectional study of patients aged ≥65 years was conducted from June 2017 to June 2018 at the Family and Community Medicine (FCM) clinics of Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 35 publications
4
28
1
4
Order By: Relevance
“…This finding is consistent with a regional study conducted in Qatar in 2019, which found an average of 8 medications per patient, along with other local studies by Alsuwaidan and Alturki in 2019 and 2020 on chronic disease patients with an average of 6.4 and 4.2 medications per patient, respectively. [ 16 17 18 ] Another recent local study considered PIMs and polypharmacy and found cases of patients that were prescribed ten or 12 PIMs at once, with more than 25% of their study population having more than five PIMs at once. [ 19 ] The number of medications can be correlated to the increased number of chronic conditions in geriatrics, along with an increased number of surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with a regional study conducted in Qatar in 2019, which found an average of 8 medications per patient, along with other local studies by Alsuwaidan and Alturki in 2019 and 2020 on chronic disease patients with an average of 6.4 and 4.2 medications per patient, respectively. [ 16 17 18 ] Another recent local study considered PIMs and polypharmacy and found cases of patients that were prescribed ten or 12 PIMs at once, with more than 25% of their study population having more than five PIMs at once. [ 19 ] The number of medications can be correlated to the increased number of chronic conditions in geriatrics, along with an increased number of surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] The number of medications can be correlated to the increased number of chronic conditions in geriatrics, along with an increased number of surgeries. [ 16 17 19 ] In addition, an Indonesian study found that the rate of PIM exposure reached 52.2% of their geriatric patients in primary care facilities was only statistically significant to polypharmacy. [ 20 ] In addition to the increased number of medications, we found increased statistical significance across all medications administered in hospital settings when compared to primary care centers, as shown in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly prescribed medications in the context of co-morbidity may also negatively impact sleep. Antihypertensives, antidepressants, antiepileptics, corticosteroids, decongestants and diuretics are among many medications that have been associated with insomnia, and may represent potentially inappropriate medications in the older patient [251][252][253][254]. The number of potentially inappropriate prescribed medications has also been associated with reduced sleep efficiency and sleep quality [255].…”
Section: Medications and Polypharmacymentioning
confidence: 99%
“…Older age, female sex, and comorbidities have all been associated with adverse drug events [23]. A number of studies have reported that women experience both increased and decreased effects from medications as well as more adverse drug events than men [24][25][26][27].…”
Section: Why the Need For A Sex And Gender Lens?mentioning
confidence: 99%